Meningkatkan Kesadaran Akan Pentingnya Sertifikasi Halal Bagi Pelaku UMKM Di Kecamatan Pontianak Barat - Desy Septiani; Fahri Fahri; Anggraini Anggraini; Titik Rosnani (Jurnal Nusantara Berbakti, 2024)
The halal lifestyle has also experienced significant development both in Indonesia and in the world. In facing the era of globalization and intense business competition, Micro, Small and Medium Enterprises (MSMEs) in West Pontianak District are required to continue to adapt to changes and meet higher quality standards. However, there is still a lack of awareness among MSME actors in the District about the importance of halal certification. This will have an impact on losing their market share, especially among people who are increasingly aware of the halality of the products they consume. The type of method for implementing community service activities is a participatory dialogue seminar which is carried out by inviting 40 selected MSME players in the district to understand more deeply the importance and how to obtain certification. It is hoped that effective strategies can be found to increase the implementation of this certification among MSMEs in this region.